Investigation of new manganese orthophosphate Mn3(PO4)2 coating for nickel-rich LiNi0.6Co0.2Mn0.2O2 cathode and improvement of its thermal properties. (20th April 2016) - Cho, Woosuk; Kim, Sang-Min; Lee, Ko-Woon; Song, Jun Ho; Jo, Yong Nam; Yim, Taeeun; Kim, Hyuntae; Kim, Jeom-Soo; Kim, Young-Jun
Abstract: In this study, manganese orthophosphate (Mn3 (PO4 )2 ) is investigated as a new coating material for the Ni-rich LiNi0.6 Co0.2 Mn0.2 O2 cathode with the aim of improving its thermal properties. A sol–gel process is employed to achieve a uniform coating of nano–sized crystalline Mn3 (PO4 )2 . The coated electrode is found to exhibit an improved rate capability at high current drain, and cycle performance is enhanced at a high temperature of 60 °C. The effect of the Mn3 (PO4 )2 coating thus formed is further investigated by AC impedance spectroscopy, the results of which confirm that interfacial impedance is significantly decreased even in the initial cycles, and the growth of impedance is successfully suppressed during progressive cycles. The thermal stability of LiNi0.6 Co0.2 Mn0.2 O2 is also improved by the Mn3 (PO4 )2 coating, because of the high structural stability attributed to strong PO4 covalent bonds. On the basis of these results, the Mn3 (PO4 )2 coating is proposed as a viable surface modification method for the enhancement of the electrochemical and thermal properties of LiNi0.6 Co0.2 Mn0.2 O2 .